Applied Research for the Construction of a Sustainable Campus at the University of Sao Paulo - Lemos, Patricia Faga Iglecias; Gomes, Tamara Maria; e Aguiar, Alexandre de Oliveira; Narvaez-Romo, Beethoven; D'Aquino, Camila Agner; Perecin, Danilo; Brando, Fernanda; Sauer, Ildo Luis; Bolanos, Julio Romel Martinez; Meneghini, Julio Romano; Camiloti, Priscila Rosseto; Zilles, Roberto; Pacca, Sergio Almeida; Coelho, Suani Teixeira; Lopes, Thiago; Junior, Carlos G. Carlotti (Universitas Diponegoro, 2025)
The University of São Paulo (USP), through its Environmental Policy and under the coordination of the Superintendence of Environmental Management (SGA), has been promoting sustainability initiatives across its campuses. One of the most recent efforts is the USP Sustainability Program (USPSusten), which supports teaching, research, outreach, and shared management activities focused on socio-environmental sustainability, carried out by faculty and postdoctoral researchers. Highlighted projects include: (a) the Bioenergy and Biofertilizer Production Plant (BBPP), which uses organic waste from campus dining halls and green areas at the main campus (CUASO) to produce biogas and fertilizers; (b) a pilot plant for fueling hydrogen-powered buses, with a range of 240 km; (c) photovoltaic energy generation, with the potential to meet up to 27% of contracted electricity demand; and (d) greenhouse gas inventories, based on the GHG Protocol methodology. The BBPP, in operation since May 2021, processes organic waste to generate an average of 2,800 kWh/month, with an average output of 136 kWh per ton of waste. The hydrogen fuel project uses ethanol as a renewable energy source and aims to reduce CO₂eq emissions per capita by up to 72% compared to conventional combustion vehicles. Solar generation has shown economic feasibility for units consuming over 100 MWh/month. The emission inventory, structured through an action-research approach, involves pilot units within USP and highlights the need for improvements in the use of refrigerant gases in buildings and anesthetic gases in hospitals. These integrated efforts demonstrate the University’s commitment to conserving natural resources and enhancing quality of life.